Amelanotic Choroidal Melanoma with Extraocular Extension in a 51 Year-Old Female: A Rare Case - Ervianti, Octarina; Lutfi, Delfitri (Vision Science and Eye Health Journal, 2024)
Introduction: Melanoma is a dangerous malignancy primarily involving the choroid, ciliary body, or iris. The most frequent primary intraocular malignant tumor is choroidal melanoma. The tumor most often affects Caucasians of Northern Europe ranging between the ages of 50 and 80. Most choroidal melanomas are pigmented, however, non-pigmented or mixed pigmented and non-pigmented forms can also happen. Compared with other amelanotic choroidal lesions, amelanotic choroidal melanoma showed markedly greater basal diameter, thickness, frequent connection with subretinal fluid, and ultrasonic hollowness. Extrascleral extension is currently detected in 10% to 28% of choroidal melanoma patients, and the mortality rate is much greater than in those without the extension. Case Presentation: We reported a rare case of extraocular extension in a 51-year-old female patient with amelanotic melanoma. The primary complaint was a painful and bleeding mass on her left eye that had developed two months prior to admission. On the conjunctiva of the left eye, there was a solid, palpable mass measuring 4 x 3.5 x 1 cm. It was red, well-defined, and had a hard, solid consistency. It was fixed at the base, had minimal bleeding, and pressed on her eyeball from the inferolateral direction. The cornea appears clear, and there is no light perception in visual acuity. The orbital focus computed tomography scan revealed an Enhancing solid mass containing a fat component. The mass was in the left intraocular, extending from intraconal to extraconal. Conclusions: Amelanotic melanoma with extraocular extension is a rare condition that can be difficult to detect due to its unclear clinical symptoms and wide range of possible causes. Patients and their families must be educated to receive the appropriate first therapy and prevent the illness from worsening. Melanoma management depends on several factors: tumor size, location, related characteristics, opposite eye status, systemic status, and patient preference. Orbital exenteration is one of the management options for choroidal melanoma with significant extraocular extension. By the time ocular treatment begins, the patient's survival may already be predetermined, and this realization could impact how uveal melanoma is treated in the years to come.